Removal of Color from Wastewater by Sorption for Water Reuse - Gupta G.S.; Prasad G.; Singh V.N. (My University, 2025)
The removal of Metomega Chrome Orange GL, a commercial textile dye from wastewaters has been found to be nearly 99% under the optimal conditions (i.e. 3.0 pH and 30°C temperature) using fly ash as an sorbent. The process follows a first order kinetics and the value of rate constant,Kadis of the order 3 x 10-2min-1. Intraparticle diffusion and mass transfer coefficients have been determined at different temperatures. The sorption data fits well in the Langmuir isotherm model. The effect of temperature has been explained on the basis of boundary layer thickness, activation energy (Ea =-0.87 Cal mol-1) and enthalpy change (ΔH =-13.04 Cal mole-1) study. Heat of sorption has been found to be a function of surface coverage. © 1988 by Marcel Dekker, Inc.